A calcium-based adsorption material for the synergistic and efficient removal of multiple pollutants from flue gas

By preparing calcium-based adsorption materials with a specific surface area of ​​40~68 m2/g, using the porous structure of calcium-aluminum composite oxide, the problem of low synergistic removal efficiency of various pollutants in flue gas is solved, and high-efficiency adsorption efficiency and Waste resource utilization.

CN118847053BActive Publication Date: 2024-12-17SOUTH CHINA INST OF ENVIRONMENTAL SCI MEP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411333407.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-17
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The prior art has low efficiency in the coordinated removal of various pollutants in flue gas, and the adsorption efficiency is only about 90%, making it difficult to effectively deal with a variety of harmful substances.

Method used

Using calcium-based adsorbent material with a specific surface area of ​​40~68 m2/g, by mixing calcium carbonate with secondary aluminum ash slag in a specific molar ratio, it is fired and activated to form a porous calcium-aluminum composite oxide, and the Large adsorption capacity.

Benefits of technology

It has achieved efficient adsorption of various harmful substances, with an adsorption efficiency of more than 95%. Through the resource utilization of secondary aluminum ash slag, a new path for waste treatment is provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a calcium-based adsorption material for the synergistic and efficient removal of multiple pollutants from flue gas, wherein the specific surface area of ​​the calcium-based adsorption material for the synergistic and efficient removal of multiple pollutants from flue gas is 40-68 m 2 / g, the molar ratio of Ca / Al is 2-8, and it is prepared by the following method: step ①: calcium carbonate and secondary aluminum ash are prepared according to the molar ratio of Ca / Al, mixed evenly and densified to obtain raw material; step ②: the raw material is fired at 850-1000℃, and then cooled and crushed to obtain the calcium-doped initial reactant; step ③: the activation solution is prepared; step ④: the activation solution is heated and stirred, and the calcium-doped initial reactant is slowly added at the same time, and the reaction is stirred and naturally cooled to room temperature, and then dried, ground, and sieved to obtain the calcium-based adsorption material for the synergistic and efficient removal of multiple pollutants from flue gas. The calcium-based adsorption material for the synergistic and efficient removal of multiple pollutants from flue gas disclosed by the present invention can achieve the adsorption of multiple harmful substances, has a large specific surface area, and has high adsorption efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of environmental protection, and in particular to a calcium-based adsorption material for synergistically and efficiently removing multiple pollutants from flue gas. Background Art

[0002] In modern industrial production, flue gas emissions are one of the important causes of environmental pollution. Flue gas usually contains a variety of pollutants, such as sulfur dioxide (SO2), HCl, HF, heavy metal elements, etc. These pollutants not only cause serious harm to the atmospheric environment, but also have adverse effects on human health. Therefore, it is of great significance to develop an adsorbent material that can efficiently remove a variety of pollutants in flue gas.

[0003] In the existing technology, the removal technology for single pollutants in flue gas is relatively mature, but the technology for the synergistic removal of multiple pollutants is still insufficient, and the adsorption efficiency is only about 90%. For example, Chinese invention patent application CN112516780A provides a calcium-based desulfurizer and its preparation method, which is made from the following raw materials: calcium carbonate, calcium hydroxide, kaolin, and pore-forming agent; the calcium carbonate uses light calcium carbonate, and the mesh size of all raw materials is controlled at 400-600 mesh. After mixing with water, it is extruded and formed, with a solid structure, not easy to produce powder, and can form a dense pore size, which can efficiently adsorb SO2. The invention solves the problem that the existing dry-based desulfurizer is easy to produce powder when used in the desulfurization tower, which increases the emission of particulate matter and has poor desulfurization effect; China invention patent application CN109012569A provides a calcium-based adsorbent and a preparation method thereof, wherein the adsorbent uses SiO2 as a carrier, CaO as an active ingredient and an alkali metal salt as a modifier; the preparation method is to first add a Ca(CH3COO)2·H2O aqueous solution to an aqueous solution of SiO2, stir and add an alkali metal salt to obtain a colloidal solid, then dry the colloidal solid, first roast it at 170-180°C for 1-2h, and then roast it at 845-855°C for 3-4h. The significant advantage of the invention is that the calcium-based adsorbent is applied to the measurement of mercury forms in industry, the operation steps are simple, the sampling and subsequent analysis and processing are convenient, and the mercury concentration sampling and measurement accuracy is high; China authorized invention patent CN104959132B discloses a preparation method of a calcium-based carbon dioxide adsorbent, which belongs to the field of high-temperature adsorption and separation of CO2. The method of the present invention uses alginic acid compounds as a base, and forms calcium alginate by composite cross-linking with a calcium source and an aluminum source, and then uses high-temperature sintering to obtain a porous calcium-based CO2 adsorbent. This type of calcium-based adsorbent has high CO2 adsorption efficiency, simple high-temperature desorption, and no significant decrease in efficiency after multiple cycles. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a calcium-based adsorption material for the synergistic and efficient removal of multiple pollutants from flue gas, which has an adsorption efficiency of more than 95% for a variety of waste gas pollutants and has high adsorption efficiency.

[0005] To achieve the above-mentioned purpose, the technical invention of the present invention is:

[0006] A calcium-based adsorption material for the synergistic and efficient removal of multiple pollutants from flue gas, wherein the specific surface area of ​​the calcium-based adsorption material for the synergistic and efficient removal of multiple pollutants from flue gas is 40-68 m 2 / g, Ca / Al molar ratio is 2-8, prepared by the following method:

[0007] Step ①: Calcium carbonate with a particle size of 200 mesh and secondary aluminum ash with a particle size of 200 mesh are mixed according to the Ca / Al molar ratio, and mixed to obtain a mixed material, and the mixed material is densified and formed to obtain a raw material;

[0008] Step ②: feeding the raw material into a muffle furnace, firing at 850-1000° C., and then cooling and crushing to a particle size of 200 meshes to obtain a calcium-doped initial reactant;

[0009] Step 3: Prepare an activator solution with a mass concentration of 0.1-2%;

[0010] Step ④: heating and stirring the activated solution, and slowly adding the calcium-doped initial reactant with a mass of 10% to 200% of the activated solution, stirring and reacting for 10 to 120 minutes, and then naturally cooling to room temperature, followed by drying, grinding, and sieving to obtain a calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas;

[0011] In step ③, the activator in the activator solution is one or a mixture of ammonium bicarbonate, ethylenediamine, diisopropylamine, triethanolamine, polypropylene glycol, sucrose, citric acid, and sodium hydroxide.

[0012] Secondary aluminum ash slag is a kind of industrial solid waste and needs to be treated separately. The present invention has found through experiments that secondary aluminum ash slag can be used for flue gas waste treatment, so secondary aluminum ash slag is selected as aggregate, providing a path for the waste resource utilization of secondary aluminum ash slag. At the same time, the Al content in secondary aluminum ash slag is about 50-70%, and the feed is obtained according to the Al content of the secondary aluminum ash slag through molar ratio / mass conversion. When the Ca / Al molar ratio is 2-8, the corresponding mass ratio of calcium carbonate to secondary aluminum ash slag is 5-15:1.

[0013] In order to ensure the harmful substance absorption effect, the Al content in the secondary aluminum ash determines how much active element Ca is added. According to experiments, excessive Ca will lead to increased selectivity of the prepared composite material, that is, the loss of the effect of removing various flue pollutants. The reason may be that the main calcium oxide content is too high, and the solid-phase reaction products of aluminum ash and Ca are not reflected. For example, the composite oxide formed by calcium aluminosilicate can absorb heavy metals, but this property is not easy to reflect if Ca is excessive; on the contrary, if Ca is insufficient, it will manifest as a decrease in removal efficiency.

[0014] Step ① and step ② have the following four functions: 1. To ensure the complete conversion of harmful substances in the secondary aluminum ash slag and eliminate the influence of existing harmful substances on subsequent adsorption performance; 2. To decompose calcium carbonate into porous calcium oxide particles and secondary aluminum ash slag particles under high temperature conditions, increase the specific surface area, and improve the reaction efficiency in step ④ and the adsorption efficiency of the final product; 3. The densification process can mix calcium carbonate and secondary aluminum ash slag at the microscopic level, thereby increasing the contact area of ​​the two particles, allowing solid-phase reaction to occur, thereby enriching the active substances. In addition to calcium oxide, a small amount of calcium aluminate, calcium aluminosilicate, etc. can be generated, paving the way for the adsorption of various pollutants; 4. As mentioned in point of action 3, the uniform dispersion at the microscopic level allows the solid-phase reaction products to be uniformly formed on the contact surface. In step ④, part of the calcium oxide that is not compounded with silicon and aluminum oxides will react with water, and the reaction of the activated product and the calcium-doped initial reactant occurs simultaneously, forming a flocculent co-precipitate on the calcium-doped initial reactant matrix, providing more capacity for the adsorption of harmful tail gas.

[0015] Preferably, the calcium carbonate in step ① is in one or more of a cone shape, a sphere or a polyhedron shape.

[0016] Calcium carbonate has a variety of microscopic morphologies, among which needle-shaped and flake-shaped morphologies are difficult to form porous structures. However, cone-shaped, spherical or polyhedral microscopic morphologies will expand due to the overflow of carbon dioxide when decomposed at high temperatures, forming a porous structure of calcium oxide or reacting with some metal oxides in secondary aluminum ash to form a porous transition metal composite oxide, which can improve the ability to capture gaseous harmful substances.

[0017] Preferably, in step ①, the densification comprises the following steps:

[0018] Step 1-1: Add the mixed material into a dry ball mill at a ball-to-material ratio of 10-15:1 and ball-mill for 0.5-3 hours to obtain a ball-milled material;

[0019] Step 1-2 is to obtain raw material by pressing or balling the ball mill material.

[0020] The functions of dry ball mill are threefold: first, further fine grinding; second, mixing the materials at the microscopic level; and third, reducing the gaps between the materials.

[0021] Preferably, in step ②, the firing includes the following heating process: in the range of 20-600°C, the heating rate is 5°C / min, above 600°C the heating rate is 3°C / min, and the holding time is 30min.

[0022] The main decomposition temperature range of spindle-shaped, spherical or polyhedral calcium carbonate is above 600°C, while the decomposition is less below 600°C. If the heating rate is too fast after 600°C, a large amount of carbon dioxide will overflow, which may destroy the porous structure.

[0023] Preferably, in step ④, 10% to 100% of the mass of the activator solution is added as calcium-doped initial reactant.

[0024] Preferably, in step ④, the heating temperature of the activator solution is 70-95°C.

[0025] Preferably, in step ④, the stirring speed is 200-800 rpm;

[0026] Preferably, in step ④, the drying temperature is 100-120°C and the sieving is 100-200 mesh.

[0027] Compared with the prior art, the present invention achieves the following beneficial effects:

[0028] It can achieve the adsorption of various harmful substances, has a large specific surface area and high adsorption efficiency.

[0029] Secondary aluminum ash slag is selected as aggregate, which is densified and fired to produce high-temperature solid-phase reaction with calcium source, generating a variety of active substances and forming a porous structure, thus increasing the adsorption capacity;

[0030] It realizes the resource utilization of waste and provides a new outlet for secondary aluminum ash slag. DETAILED DESCRIPTION

[0031] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1: A calcium-based adsorption material for efficient removal of multiple pollutants from flue gas, with a specific surface area of ​​65 m 2 / g, with a Ca / Al molar ratio of 5.4, was prepared by the following method:

[0033] Step ①: Mix the spun cone calcium carbonate with a particle size of 200 mesh and the secondary aluminum ash slag with a particle size of 200 mesh in a mass ratio of 12:1 to obtain a mixed material, and densify the mixed material to obtain a raw material. The densification molding includes the following steps:

[0034] Step 1-1: Add the mixed material into a dry ball mill at a ball-to-material ratio of 13:1 and ball-mill for 1 hour to obtain a ball-milled material;

[0035] Step 1-2: the ball mill is pressed under a pressure of 5 MPa to obtain a raw material;

[0036] Step ②: feeding the raw material into a muffle furnace and firing at 1000°C, wherein the heating rate in the range of 20-600°C is 5°C / min, the heating rate above 600°C is 3°C / min, and the holding time is 30min; then cooling and crushing to a particle size of 200 mesh to obtain a calcium-doped initial reactant;

[0037] Step ③: prepare an activator solution with a mass concentration of 1.5%, wherein the activator is sucrose, citric acid and sodium hydroxide in a mass ratio of 1:1:1;

[0038] Step ④: Heat and stir the activator solution to make the heating temperature of the activator solution 80°C, and at the same time slowly add calcium-doped initial reactants with a mass of 50% of the activator solution, stir the reaction at 500 rpm for 30 minutes, then naturally cool to room temperature, then dry at 110°C, grind, and pass through a 120-mesh sieve to obtain a calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas.

[0039] Example 2: A calcium-based adsorption material for efficient removal of multiple pollutants from flue gas, with a specific surface area of ​​58 m 2 / g, the molar ratio of Ca / Al is 6.75, and it is prepared by the following method:

[0040] Step ①: Mix the spun cone calcium carbonate with a particle size of 200 mesh and the secondary aluminum ash slag with a particle size of 200 mesh in a mass ratio of 12:1 to obtain a mixed material, and densify the mixed material to obtain a raw material. The densification molding includes the following steps:

[0041] Step 1-1: Add the mixed material into a dry ball mill at a ball-to-material ratio of 13:1 and ball-mill for 1 hour to obtain a ball-milled material;

[0042] Step 1-2: the ball mill is pressed under a pressure of 5 MPa to obtain a raw material;

[0043] Step ②: feeding the raw material into a muffle furnace and firing at 1000°C, wherein the heating rate in the range of 20-600°C is 5°C / min, the heating rate above 600°C is 3°C / min, and the holding time is 30min; then cooling and crushing to a particle size of 200 mesh to obtain a calcium-doped initial reactant;

[0044] Step ③: prepare an activator solution with a mass concentration of 1.5%, wherein the activator is sucrose, citric acid and sodium hydroxide in a mass ratio of 1:1:1;

[0045] Step ④: Heat and stir the activator solution to make the heating temperature of the activator solution 80°C, and at the same time slowly add calcium-doped initial reactants with a mass of 50% of the activator solution, stir the reaction at 500 rpm for 30 minutes, then naturally cool to room temperature, then dry at 110°C, grind, and pass through a 120-mesh sieve to obtain a calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas.

[0046] Example 3: A calcium-based adsorption material for efficient removal of multiple pollutants from flue gas, with a specific surface area of ​​63 m 2 / g, with a Ca / Al molar ratio of 5.4, was prepared by the following method:

[0047] Step ①: Mix the spun cone calcium carbonate with a particle size of 200 mesh and the secondary aluminum ash slag with a particle size of 200 mesh in a mass ratio of 12:1 to obtain a mixed material, and densify the mixed material to obtain a raw material. The densification molding includes the following steps:

[0048] Step 1-1: Add the mixed material into a dry ball mill at a ball-to-material ratio of 13:1 and ball-mill for 1 hour to obtain a ball-milled material;

[0049] Step 1-2: the ball mill is pressed under a pressure of 5 MPa to obtain a raw material;

[0050] Step ②: feeding the raw material into a muffle furnace and firing at 1000°C, wherein the heating rate in the range of 20-600°C is 5°C / min, the heating rate above 600°C is 3°C / min, and the holding time is 30min; then cooling and crushing to a particle size of 200 mesh to obtain a calcium-doped initial reactant;

[0051] Step ③: prepare an activator solution with a mass concentration of 1.5%, wherein the activator is sucrose, citric acid and sodium hydroxide in a mass ratio of 1:1:1;

[0052] Step ④: Heat and stir the activator solution to a temperature of 80°C, and slowly add a calcium-doped initial reactant whose mass is 100% of the activator solution. Stir the reaction at 500 rpm for 30 minutes and then naturally cool to room temperature. Then dry at 110°C, grind, and pass through a 120-mesh sieve to obtain a calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas.

[0053] Example 4: A calcium-based adsorption material for efficient removal of multiple pollutants from flue gas, with a specific surface area of ​​57 m 2 / g, with a Ca / Al molar ratio of 5.4, was prepared by the following method:

[0054] Step ①: Mix the spun cone calcium carbonate with a particle size of 200 mesh and the secondary aluminum ash slag with a particle size of 200 mesh in a mass ratio of 12:1 to obtain a mixed material, and densify the mixed material to obtain a raw material. The densification molding includes the following steps:

[0055] Step 1-1: Add the mixed material into a dry ball mill at a ball-to-material ratio of 13:1 and ball-mill for 1 hour to obtain a ball-milled material;

[0056] Step 1-2: the ball mill is pressed under a pressure of 5 MPa to obtain a raw material;

[0057] Step ②: feeding the raw material into a muffle furnace and firing at 850°C, wherein the heating rate in the range of 20-600°C is 5°C / min, the heating rate above 600°C is 3°C / min, and the holding time is 30min; then cooling and crushing to a particle size of 200 mesh to obtain a calcium-doped initial reactant;

[0058] Step ③: prepare an activator solution with a mass concentration of 1.5%, wherein the activator is sucrose, citric acid and sodium hydroxide in a mass ratio of 1:1:1;

[0059] Step ④: Heat and stir the activator solution to make the heating temperature of the activator solution 80°C, and at the same time slowly add calcium-doped initial reactants with a mass of 50% of the activator solution, stir the reaction at 500 rpm for 30 minutes, then naturally cool to room temperature, then dry at 110°C, grind, and pass through a 120-mesh sieve to obtain a calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas.

[0060] Example 5: A calcium-based adsorption material for efficient removal of multiple pollutants from flue gas, with a specific surface area of ​​60 m 2 / g, with a Ca / Al molar ratio of 5.4, was prepared by the following method:

[0061] Step ①: Mix the spun cone calcium carbonate with a particle size of 200 mesh and the secondary aluminum ash slag with a particle size of 200 mesh in a mass ratio of 12:1 to obtain a mixed material, and densify the mixed material to obtain a raw material. The densification molding includes the following steps:

[0062] Step 1-1: Add the mixed material into a dry ball mill at a ball-to-material ratio of 13:1 and ball-mill for 1 hour to obtain a ball-milled material;

[0063] Step 1-2: the ball mill is pressed under a pressure of 5 MPa to obtain a raw material;

[0064] Step ②: feeding the raw material into a muffle furnace and firing at 1000°C, wherein the heating rate in the range of 20-600°C is 5°C / min, the heating rate above 600°C is 3°C / min, and the holding time is 30min; then cooling and crushing to a particle size of 200 mesh to obtain a calcium-doped initial reactant;

[0065] Step ③: prepare an activator solution with a mass concentration of 1.5%, wherein the activator is sucrose, citric acid and sodium hydroxide in a mass ratio of 1:1:1;

[0066] Step ④: Heat and stir the activator solution to a temperature of 95°C, and slowly add calcium-doped initial reactants with a mass of 10% of the activator solution. Stir the reaction at 800 rpm for 30 minutes, then naturally cool to room temperature, then dry at 110°C, grind, and pass through a 120-mesh sieve to obtain a calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas.

[0067] Example 6: A calcium-based adsorption material for efficient removal of multiple pollutants from flue gas, with a specific surface area of ​​66 m 2 / g, with a Ca / Al molar ratio of 5.4, was prepared by the following method:

[0068] Step ①: Mix the spun cone calcium carbonate with a particle size of 200 mesh and the secondary aluminum ash slag with a particle size of 200 mesh in a mass ratio of 12:1 to obtain a mixed material, and densify the mixed material to obtain a raw material. The densification molding includes the following steps:

[0069] Step 1-1: Add the mixed material into a dry ball mill at a ball-to-material ratio of 13:1 and ball-mill for 1 hour to obtain a ball-milled material;

[0070] Step 1-2: the ball mill is pressed under a pressure of 5 MPa to obtain a raw material;

[0071] Step ②: feeding the raw material into a muffle furnace and firing at 1000°C, wherein the heating rate in the range of 20-600°C is 5°C / min, the heating rate above 600°C is 3°C / min, and the holding time is 30min; then cooling and crushing to a particle size of 200 mesh to obtain a calcium-doped initial reactant;

[0072] Step ③: prepare an activator solution with a mass concentration of 1.5%, wherein the activator is sucrose, citric acid and sodium hydroxide in a mass ratio of 1:1:1;

[0073] Step ④: Heat and stir the activator solution to a temperature of 80°C, and slowly add a calcium-doped initial reactant with a mass of 50% of the activator solution. Stir the reaction at 500 rpm for 30 minutes, then naturally cool to room temperature, then dry at 110°C, grind, and pass through a 100-mesh sieve to obtain a calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas.

[0074] Comparative Example 1: Commercially available flue gas pollutant adsorption material.

[0075] Comparative Example 2: A calcium-based adsorption material for the synergistic and efficient removal of multiple pollutants from flue gas, with a specific surface area of ​​39 m 2 / g, the molar ratio of Ca / Al is 9, and it is prepared by the following method:

[0076] Step ①: Mix the spun cone calcium carbonate with a particle size of 200 mesh and the secondary aluminum ash slag with a particle size of 200 mesh in a mass ratio of 20:1 to obtain a mixed material, and densify the mixed material to obtain a raw material. The densification molding includes the following steps:

[0077] Step 1-1: Add the mixed material into a dry ball mill at a ball-to-material ratio of 13:1 and ball-mill for 1 hour to obtain a ball-milled material;

[0078] Step 1-2: the ball mill is pressed under a pressure of 5 MPa to obtain a raw material;

[0079] Step ②: feeding the raw material into a muffle furnace and firing at 1000°C, wherein the heating rate in the range of 20-600°C is 5°C / min, the heating rate above 600°C is 3°C / min, and the holding time is 30min; then cooling and crushing to a particle size of 200 mesh to obtain a calcium-doped initial reactant;

[0080] Step ③: prepare an activator solution with a mass concentration of 1.5%, wherein the activator is sucrose, citric acid and sodium hydroxide in a mass ratio of 1:1:1;

[0081] Step ④: Heat and stir the activator solution to make the heating temperature of the activator solution 80°C, and at the same time slowly add calcium-doped initial reactants with a mass of 50% of the activator solution, stir the reaction at 500 rpm for 30 minutes, then naturally cool to room temperature, then dry at 110°C, grind, and pass through a 120-mesh sieve to obtain a calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas.

[0082] Comparative Example 3: A calcium-based adsorption material for efficient removal of multiple pollutants from flue gas, with a specific surface area of ​​35 m 2 / g, the molar ratio of Ca / Al is 1.8, and it is prepared by the following method:

[0083] Step ①: Mix the spun cone calcium carbonate with a particle size of 200 mesh and the secondary aluminum ash slag with a particle size of 200 mesh in a mass ratio of 4:1 to obtain a mixed material, and densify the mixed material to obtain a raw material. The densification molding includes the following steps:

[0084] Step 1-1: Add the mixed material into a dry ball mill at a ball-to-material ratio of 13:1 and ball-mill for 1 hour to obtain a ball-milled material;

[0085] Step 1-2: the ball mill is pressed under a pressure of 5 MPa to obtain a raw material;

[0086] Step ②: feeding the raw material into a muffle furnace and firing at 1000°C, wherein the heating rate in the range of 20-600°C is 5°C / min, the heating rate above 600°C is 3°C / min, and the holding time is 30min; then cooling and crushing to a particle size of 200 mesh to obtain a calcium-doped initial reactant;

[0087] Step ③: prepare an activator solution with a mass concentration of 1.5%, wherein the activator is sucrose, citric acid and sodium hydroxide in a mass ratio of 1:1:1;

[0088] Step ④: Heat and stir the activator solution to make the heating temperature of the activator solution 80°C, and at the same time slowly add calcium-doped initial reactants with a mass of 50% of the activator solution, stir the reaction at 500 rpm for 30 minutes, then naturally cool to room temperature, then dry at 110°C, grind, and pass through a 120-mesh sieve to obtain a calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas.

[0089] Comparative Example 4: A calcium-based adsorption material for efficient removal of multiple pollutants from flue gas, with a specific surface area of ​​41 m 2 / g, with a Ca / Al molar ratio of 5.4, was prepared by the following method:

[0090] Step ①: mixing needle-shaped calcium carbonate with a particle size of 200 mesh and secondary aluminum ash slag with a particle size of 200 mesh in a mass ratio of 12:1 to obtain a mixed material, and densifying and molding the mixed material to obtain a raw material, wherein the densification molding comprises the following steps:

[0091] Step 1-1: Add the mixed material into a dry ball mill at a ball-to-material ratio of 13:1 and ball-mill for 1 hour to obtain a ball-milled material;

[0092] Step 1-2: the ball mill is pressed under a pressure of 5 MPa to obtain a raw material;

[0093] Step ②: feeding the raw material into a muffle furnace and firing at 1000°C, wherein the heating rate in the range of 20-600°C is 5°C / min, the heating rate above 600°C is 3°C / min, and the holding time is 30min; then cooling and crushing to a particle size of 200 mesh to obtain a calcium-doped initial reactant;

[0094] Step ③: prepare an activator solution with a mass concentration of 1.5%, wherein the activator is sucrose, citric acid and sodium hydroxide in a mass ratio of 1:1:1;

[0095] Step ④: Heat and stir the activator solution to make the heating temperature of the activator solution 80°C, and at the same time slowly add calcium-doped initial reactants with a mass of 50% of the activator solution, stir the reaction at 500 rpm for 30 minutes, then naturally cool to room temperature, then dry at 110°C, grind, and pass through a 120-mesh sieve to obtain a calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas.

[0096] Comparative Example 5: A calcium-based adsorption material for efficient removal of multiple pollutants from flue gas, with a specific surface area of ​​36 m 2 / g, with a Ca / Al molar ratio of 5.4, was prepared by the following method:

[0097] Step ①: Mix the spun cone calcium carbonate with a particle size of 200 mesh and the secondary aluminum ash slag with a particle size of 200 mesh in a mass ratio of 12:1 to obtain a mixed material, and densify the mixed material to obtain a raw material. The densification molding includes the following steps:

[0098] Step 1-1: Add the mixed material into a dry ball mill at a ball-to-material ratio of 13:1 and ball-mill for 1 hour to obtain a ball-milled material;

[0099] Step 1-2: the ball mill is pressed under a pressure of 5 MPa to obtain a raw material;

[0100] Step ②: feeding the raw material into a muffle furnace and firing at 1100°C, wherein the heating rate in the range of 20-600°C is 5°C / min, the heating rate above 600°C is 3°C / min, and the holding time is 30min; then cooling and crushing to a particle size of 200 mesh to obtain a calcium-doped initial reactant;

[0101] Step ③: prepare an activator solution with a mass concentration of 1.5%, wherein the activator is sucrose, citric acid and sodium hydroxide in a mass ratio of 1:1:1;

[0102] Step ④: Heat and stir the activator solution to make the heating temperature of the activator solution 80°C, and at the same time slowly add calcium-doped initial reactants with a mass of 50% of the activator solution, stir the reaction at 500 rpm for 30 minutes, then naturally cool to room temperature, then dry at 110°C, grind, and pass through a 120-mesh sieve to obtain a calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas.

[0103] Comparative Example 6: A calcium-based adsorption material for efficient removal of multiple pollutants from flue gas, with a specific surface area of ​​25 m 2 / g, with a Ca / Al molar ratio of 5.4, was prepared by the following method:

[0104] Step ①: Mix the spun cone calcium carbonate with a particle size of 200 mesh and the secondary aluminum ash slag with a particle size of 200 mesh in a mass ratio of 12:1 to obtain a mixed material, and densify the mixed material to obtain a raw material. The densification molding includes the following steps:

[0105] Step 1-1: Add the mixed material into a dry ball mill at a ball-to-material ratio of 13:1 and ball-mill for 1 hour to obtain a ball-milled material;

[0106] Step 1-2: the ball mill is pressed under a pressure of 5 MPa to obtain a raw material;

[0107] Step ②: feeding the raw material into a muffle furnace and firing at 800°C, wherein the heating rate in the range of 20-600°C is 5°C / min, the heating rate above 600°C is 3°C / min, and the holding time is 30min; then cooling and crushing to a particle size of 200 mesh to obtain a calcium-doped initial reactant;

[0108] Step ③: prepare an activator solution with a mass concentration of 1.5%, wherein the activator is sucrose, citric acid and sodium hydroxide in a mass ratio of 1:1:1;

[0109] Step ④: Heat and stir the activator solution to make the heating temperature of the activator solution 80°C, and at the same time slowly add calcium-doped initial reactants with a mass of 50% of the activator solution, stir the reaction at 500 rpm for 30 minutes, then naturally cool to room temperature, then dry at 110°C, grind, and pass through a 120-mesh sieve to obtain a calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas.

[0110] Comparative Example 7: A calcium-based adsorption material for efficient removal of multiple pollutants from flue gas, with a specific surface area of ​​57 m 2 / g, with a Ca / Al molar ratio of 5.4, was prepared by the following method:

[0111] Step ①: Mix the spun cone calcium carbonate with a particle size of 200 mesh and the secondary aluminum ash slag with a particle size of 200 mesh in a mass ratio of 12:1 to obtain a mixed material, and densify the mixed material to obtain a raw material. The densification molding includes the following steps:

[0112] Step 1-1: Add the mixed material into a dry ball mill at a ball-to-material ratio of 13:1 and ball-mill for 1 hour to obtain a ball-milled material;

[0113] Step 1-2: the ball mill is pressed under a pressure of 5 MPa to obtain a raw material;

[0114] Step ②: feeding the raw material into a muffle furnace and firing at 1000°C, wherein the heating rate in the range of 20-600°C is 5°C / min, the heating rate above 600°C is 3°C / min, and the holding time is 30min; then cooling and crushing to a particle size of 200 mesh to obtain a calcium-doped initial reactant;

[0115] Step ③: prepare an activator solution with a mass concentration of 1.5%, wherein the activator is sucrose, citric acid and sodium hydroxide in a mass ratio of 1:1:1;

[0116] Step ④: Heat and stir the activator solution to a temperature of 80°C, and slowly add calcium-doped initial reactants with a mass of 5% of the activator solution. Stir the reaction at 500 rpm for 30 minutes, then naturally cool to room temperature, then dry at 110°C, grind, and pass through a 120-mesh sieve to obtain a calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas.

[0117] Comparative Example 8: A calcium-based adsorption material for efficient removal of multiple pollutants from flue gas, with a specific surface area of ​​50 m 2 / g, with a Ca / Al molar ratio of 5.4, was prepared by the following method:

[0118] Step ①: Mix the spun cone calcium carbonate with a particle size of 200 mesh and the secondary aluminum ash slag with a particle size of 200 mesh in a mass ratio of 12:1 to obtain a mixed material, and densify the mixed material to obtain a raw material. The densification molding includes the following steps:

[0119] Step 1-1: Add the mixed material into a dry ball mill at a ball-to-material ratio of 13:1 and ball-mill for 1 hour to obtain a ball-milled material;

[0120] Step 1-2: the ball mill is pressed under a pressure of 5 MPa to obtain a raw material;

[0121] Step ②: feeding the raw material into a muffle furnace and firing at 1000°C, wherein the heating rate in the range of 20-600°C is 5°C / min, the heating rate above 600°C is 3°C / min, and the holding time is 30min; then cooling and crushing to a particle size of 200 mesh to obtain a calcium-doped initial reactant;

[0122] Step ③: Heat and stir deionized water to 80°C, and slowly add calcium-doped initial reactants with a mass of 50% of deionized water. Stir the reaction at 500 rpm for 30 minutes and then naturally cool to room temperature. Then dry at 110°C, grind, and pass through a 120-mesh sieve to obtain a calcium-based adsorption material that can synergistically and efficiently remove multiple pollutants from flue gas.

[0123] Comparative Example 9: A calcium-based adsorption material for efficient removal of multiple pollutants from flue gas, with a specific surface area of ​​56 m 2 / g, with a Ca / Al molar ratio of 5.4, was prepared by the following method:

[0124] Step ①: mixing the spun cone calcium carbonate with a particle size of 200 mesh and the secondary aluminum ash slag with a particle size of 200 mesh in a mass ratio of 12:1 to obtain a mixed material;

[0125] Step ②: feeding the mixed material into a muffle furnace and firing at 1000°C, wherein the heating rate in the range of 20-600°C is 5°C / min, the heating rate above 600°C is 3°C / min, and the holding time is 30min; then cooling and crushing to a particle size of 200 mesh to obtain a calcium-doped initial reactant;

[0126] Step ③: prepare an activator solution with a mass concentration of 1.5%, wherein the activator is sucrose, citric acid and sodium hydroxide in a mass ratio of 1:1:1;

[0127] Step ④: Heat and stir the activator solution to make the heating temperature of the activator solution 80°C, and at the same time slowly add calcium-doped initial reactants with a mass of 50% of the activator solution, stir the reaction at 500 rpm for 30 minutes, then naturally cool to room temperature, then dry at 110°C, grind, and pass through a 120-mesh sieve to obtain a calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas.

[0128] The aluminum content in the secondary aluminum ash slag selected in the above embodiments and comparative examples is 60%.

[0129] Comparative Example 10: The difference from Example 1 is that no secondary aluminum ash slag is used, and the comparative example 10 is prepared by the following method:

[0130] Step ①: densifying and molding the spun cone calcium carbonate with a particle size of 200 mesh to obtain raw material, wherein the densification molding comprises the following steps:

[0131] Step 1-1: Add the mixed material into a dry ball mill at a ball-to-material ratio of 13:1 and ball-mill for 1 hour to obtain a ball-milled material;

[0132] Step 1-2: the ball mill is pressed under a pressure of 5 MPa to obtain a raw material;

[0133] Step ②: feeding the raw material into a muffle furnace and firing at 1000°C, wherein the heating rate in the range of 20-600°C is 5°C / min, the heating rate above 600°C is 3°C / min, and the holding time is 30min; then cooling and crushing to a particle size of 200 mesh to obtain calcium oxide;

[0134] Step ③: prepare an activator solution with a mass concentration of 1.5%, wherein the activator is sucrose, citric acid and sodium hydroxide in a mass ratio of 1:1:1;

[0135] Step ④: Heat and stir the activator solution to a temperature of 80°C, and slowly add calcium oxide in an amount of 50% of the mass of the activator solution. Stir the reaction at 500 rpm for 30 minutes, then naturally cool to room temperature, and then dry at 110°C, grind, and pass through a 120-mesh sieve to obtain a calcium-based adsorption material.

[0136] Performance Test:

[0137] 1. Harmful gas adsorption test: The same mass of the calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas prepared in the above Examples 1-6 and the adsorption material described in Comparative Examples 1-8 were filled in a drying tube, a mixed gas of a fixed composition (N2, O2, CO2, SO2, HCl and HF mixed gas with mass ratios of 60%, 10%, 15%, 6%, 5% and 4% respectively) was introduced into one end of the drying tube, and a gas composition detection device was introduced into the other end. The data obtained are shown in Table 1.

[0138] 2. Heavy metal ion adsorption test: Since it is difficult to obtain heavy metals in tail gas and difficult to achieve in the laboratory, the present invention will characterize the adsorption efficiency by measuring the amount of heavy metal adsorption in the solution. 10g of the flue gas multi-pollutant synergistic and efficient removal calcium-based adsorption material prepared in the above Examples 1-6 and the adsorption material described in Comparative Examples 1-8 are placed in a beaker, and 200mL of a mixed heavy metal salt solution with fixed components is added to the beaker. The main heavy metals are Hg 2+ , Cu 2+ and Pb 2+ , the corresponding concentrations are 0.05mol / L, 0.1mol / L and 0.05mol / L, the solution pH is 4, and the filtrate is filtered after 30 minutes to test the concentrations of the three heavy metal ions in the filtrate. Due to the presence of alkaline oxides such as calcium oxide on the surface of the adsorption material, it will react with the water in the solution, which is quite different from the actual exhaust gas working conditions. Therefore, the experimental results only provide a reference for the heavy metal adsorption capacity for practical applications.

[0139] Table 1 Adsorption test results of calcium-based adsorption materials

[0140]

[0141] In the above-mentioned Examples 1-6, the absorption of harmful gases in simulated exhaust gas is higher than 95% for sulfide, and even exceeds 99% for hydrogen halide. The absorption rate of carbon dioxide is also over 85%. These three gases are collectively referred to as acidic gases hereinafter. The adsorption efficiency of heavy metals is over 99%.

[0142] Comparative Example 1 is a commercially available tail gas adsorbent, which has an insignificant effect on heavy metal removal and is less efficient in adsorbing acidic tail gas than Examples 1-6.

[0143] Comparative Examples 2 and 3 illustrate the importance of setting the molar ratio range in the present invention. When the molar ratio is too high, not only the absorption efficiency of acidic gases decreases, but also the absorption efficiency of heavy metals is not ideal. The reason may be that excessive calcium oxide reacts with water to generate a calcium hydroxide film that covers the composite oxide structure of calcium oxide and the matrix, thereby greatly reducing the heavy metal absorption capacity; Comparative Example 3 shows a good adsorption effect on heavy metals, but in the gas adsorption test, its calcium oxide is insufficient and the absorption efficiency of acidic gases is low.

[0144] Comparative Example 4 shows that the morphology of calcium carbonate will affect the morphology of the final product. Needle-shaped calcium carbonate decomposes into dispersed calcium oxide particles, which have a small particle size but a nearly smooth surface, thus affecting the specific surface area and reducing the adsorption capacity of acidic gases.

[0145] Comparative Examples 5 and 6 are over-burned and under-burned. When over-burned, the grains are coarse and the surface porous structure is closed, which reduces the overall adsorption area; while when under-burned, not only the microporous structure is not formed, but the solid phase reaction is also not completed, so the adsorption efficiency is low.

[0146] Comparative Example 7 is a case where the activator is excessive. Although the activator is excessive, it still has a good adsorption effect, but it increases the production cost. At the same time, some side reactions will occur between the excessive activator and the calcium-doped initial reactant, resulting in excessive Ca 2+ The ions enter the solution, and excessive inactive salts are generated during the drying process, resulting in reduced gas absorption efficiency.

[0147] Comparative Example 8 is the result of treatment without an activator. It can be seen that treatment without an activator has a greater impact on exhaust gas absorption, but less impact on heavy metal absorption. This once again proves that calcium aluminum composite oxide in the adsorption material is very important for the adsorption of heavy metals, and the activator has a greater impact on gas absorption efficiency.

[0148] Comparative Example 9 directly fired the calcium-doped initial reactant without the densification step. This process prevented the mixed materials from being mixed and contacted at the micron scale, which limited the solid phase reaction. Therefore, the adsorption material finally obtained was not highly active and had low adsorption performance, especially for heavy metals. At the same time, the pressure during the pressing of the raw material should not be too high, preferably 5-10 MPa. Too high pressure will not easily generate a porous structure.

[0149] The effect of Comparative Example 10 is similar to that of soda lime in conventional laboratories and cannot meet the needs of industrial production. The reasons may be as follows: ① The specific surface area is small and the adsorption effect (adsorption capacity) is poor; ② The reaction products cover the surface of the reactants and prevent the reaction from continuing. The calcium-based adsorption material for the synergistic and efficient removal of multiple pollutants from flue gas proposed in the present invention has a high specific surface area, a large adsorption capacity, and many active sites. It captures harmful gases more through the coordination structure and electrostatic force of exposed metal atoms, so it is essentially different from Comparative Example 10.

[0150] In summary, the calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas described in the present invention has a higher specific surface area and complex material structure than general materials, has a universal adsorption effect on the treatment of exhaust gas, and has the characteristics of high adsorption efficiency.

[0151] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical invention and the inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A calcium-based adsorption material for efficient removal of multiple pollutants from flue gas, characterized in that: The specific surface area of ​​the calcium-based adsorption material for efficient synergistic removal of multiple pollutants from flue gas is 40-68 m 2 / g, the molar ratio of Ca / Al is 2-8, and is prepared by the following method: Step ①: Calcium carbonate with a particle size of 200 mesh and secondary aluminum ash with a particle size of 200 mesh are mixed according to the Ca / Al molar ratio, and mixed to obtain a mixed material, and the mixed material is densified and formed to obtain a raw material; Step ②: feeding the raw material into a muffle furnace, firing at 850-1000° C., and then cooling and crushing to a particle size of 200 meshes to obtain a calcium-doped initial reactant; Step 3: Prepare an activator solution with a mass concentration of 0.1-2%; Step ④: heating and stirring the activated solution, and slowly adding the calcium-doped initial reactant with a mass of 10% to 200% of the activated solution, stirring and reacting for 10 to 120 minutes, and then naturally cooling to room temperature, followed by drying, grinding, and sieving to obtain a calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas; In step ③, the activator in the activator solution is one or a mixture of ammonium bicarbonate, ethylenediamine, diisopropylamine, triethanolamine, polypropylene glycol, sucrose, citric acid, and sodium hydroxide; The densification molding comprises the following steps: Step 1-1: Add the mixed material into a dry ball mill at a ball-to-material ratio of 10-15:1 and ball-mill for 0.5-3 hours to obtain a ball-milled material; Step 1-2: the ball mill material is pressed or balled to obtain raw material; In step ②, the firing includes the following heating process: in the range of 20-600°C, the heating rate is 5°C / min, above 600°C, the heating rate is 3°C / min, and the holding time is 30min; In step ④, 10% to 100% of the mass of the activator solution is added to the initial reactant doped with calcium; The heating temperature of the activated solution is 70~95℃.

2. The calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas according to claim 1 is characterized in that: The calcium carbonate is in one or more of a spindle cone, a sphere or a polyhedron.

3. The calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas according to claim 1 is characterized in that: In step ④, the stirring speed is 200-800 rpm.

4. The calcium-based adsorption material for synergistic and efficient removal of multiple pollutants from flue gas according to claim 1 is characterized in that: In the step ④, the drying temperature is 100-120° C. and the sieving is 100-200 mesh.